Assessment and monitoring of energy adaptivity characteristics of buildings at the stages of practical implementation and improvement - Donenko, V. (Ways to Improve Construction Efficiency, 2025)
Ensuring the energy adaptivity of buildings is emerging as a key direction for improving the efficiency of facility operation under changing environmental conditions. The complexity of modern engineering systems, variability of usage modes, and the influence of external factors necessitate a transition to dynamic approaches for evaluating energy performance. In this context, the integration of assessment and monitoring procedures becomes particularly important, as it enables the formation of a comprehensive understanding of a building’s condition and its capacity for adaptation. Energy adaptivity is considered an integral property reflecting a building’s ability to adjust its energy consumption parameters in accordance with operating conditions while maintaining the required level of comfort and efficiency. Its quantitative determination requires the use of a system of interrelated indicators that take into account technical, operational, and economic aspects. The development of such indicators enables comprehensive assessment and provides a foundation for informed decision-making. Monitoring serves as a tool for continuous observation of energy parameters, ensuring the collection and analysis of data in real time. This creates opportunities for the timely detection of deviations, evaluation of trends, and forecasting of changes in building performance. An essential component is the application of digital technologies, which allow the integration of heterogeneous data flows and improve the accuracy of analytical procedures. The combination of assessment and monitoring forms the basis for implementing adaptive management aimed at enhancing energy efficiency and ensuring the stability of building operation. The application of these approaches contributes to the optimization of energy consumption, reduction of operational costs, and improvement of the reliability of engineering systems. At the same time, the effectiveness of such approaches largely depends on the quality of information support, the level of process automation, and the ability of management systems to process large volumes of data. An important aspect is also the alignment of technical solutions with their economic feasibility, which involves evaluating the effects of adaptive measures in the long term. The formation of integrated management mechanisms for energy characteristics of buildings makes it possible to increase their resilience to environmental changes, ensure rational use of resources, and improve operational quality. Such an approach creates prerequisites for the development of innovative building management models and enhances their competitiveness in the modern market.